Estudio de la interconectividad y seguridad de datos del gad_municipal de Baba - Vera Mejia, Maria Mercedes (2019)
Interconnectivity is the communication of two or more networks connected to each other. The protection of data is of vital importance, since it depends on the execution of the tasks of each of the departments that make up the institution, which should always be safe and feasible information, The Municipal GAD of the Baba Canton is one of The oldest cantons in the Province of Los Ríos, is an entity that belongs to the public sector, with administrative and financial autonomy, this institution is made up of twelve departments, which are technologically interconnected so there is no effective and safe communication of the information that is generated in the units that make up the GAD Baba. Currently, every organization has an Information Network infrastructure and is known as ICT, in terms of the topology used in the Municipal Decentralized Autonomous Government of the Baba canton is a Tree type. The distribution of the equipment and terminals is determined thanks to a switch, from which cable branches come out. The wiring used is UTP category 5 and 6, its installation does not have conduits, distributed for the 12 terminals that have the Windows 7 operating system. The Nmap tool was applied to identify the threats and vulnerabilities that exist, within the threats found in the institution, it is found that the network is not in accordance with the quality standards established to protect the information circulating through that medium . Three security policies that are under approval analysis have been identified, managed by the Information Security Management. After the policy was implemented, a new evaluation was carried out to determine if the policy has been helpful in mitigating the problems encountered through the proposed scenarios